2016
DOI: 10.1177/0267658316641725
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Expressions: Productive syntax in the L2 acquisition of formulaic language

Abstract: This article presents a generative analysis of the acquisition of formulaic language as an alternative to current usage-based proposals. One influential view of the role of formulaic expressions in second language (L2) development is that they are a bootstrapping mechanism into the L2 grammar; an initial repertoire of constructions allows for statistical induction of abstract grammatical categories, such that formulaic language is the data source from which syntactic rules are derived. This study brings eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…The repeated use of formulas in writing and role play fortified them in the students' schema for automatic use later, at a time of need. Formulas usage supports Bardovi-Harlig's and Stringer's (2017) findings that formulas get stored with conventional phrases in long term memory.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The repeated use of formulas in writing and role play fortified them in the students' schema for automatic use later, at a time of need. Formulas usage supports Bardovi-Harlig's and Stringer's (2017) findings that formulas get stored with conventional phrases in long term memory.…”
Section: Discussionsupporting
confidence: 65%
“…The view that once the formulaic expressions are memorised they help in the induction of abstract grammatical constructions has been advocated by Ellis ( , 2012 and Wray (2000Wray ( , 2008. Contrary to this view is the one that as learners develop their language proficiency, their knowledge of syntax and lexis drives changes in the production of conventional expressions and multi-word expressions-formulaic expressions (Bardovi-Harlig & Stringer, 2017). Nevertheless, the importance of formulaic expressions cannot be underestimated.…”
Section: Introductionmentioning
confidence: 95%
“…Attempts at the conventional expressions, or the lexical core, exhibit at least two content words of a multi‐morpheme expression but are not identical to the conventional expression. The lexical core is a concept from second language acquisition derived from interlanguage analysis (Bardovi–Harlig, ; Bardovi–Harlig & Stringer, ; see also Taguchi et al., ). In English, Sorry for lating shows sorry and late , the lexical core for Sorry I'm late ; in Chinese, the lexical core for “X shì duōshǎo qián ” (‘How much is X?’) is duōshǎo ‘how much’ and qián ‘money.’ Interrater reliability for the identification of the lexical core of target expressions was 90.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of lower‐scoring scenarios showed that learners may have performed different speech acts in those contexts, or if they performed the expected speech act, may have used a competing expression. The subsequent interlanguage analysis showed that learners start with a lexical core—key words that carry the meaning of the expression—such as sorry … late for the conventional expression Sorry I'm late which fills in as the grammar develops (Bardovi–Harlig & Stringer, ). In a second study, Bardovi–Harlig and Bastos () investigated the influence of proficiency, length of stay, and intensity of interaction on the production of conventional expressions by the learners in Bardovi–Harlig ().…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation